PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS V SEKOLAH DASAR - Apsari, Gerrid Mei; Nurhayati, Eni; Sandra Dewi , Anggralita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research was to determine the feasibility of scrapbook learning media and improve student learning outcomes. Scrapbook is a collection of pictures or photos collected into one resembling a photo album that is creatively decorated to make it more interesting. This type of research is an R&D (Research and Development) with the ADDIE model, which consists of five stages, namely, analysis, design, development, implementation, and evaluation. This research uses data collection techniques in the form of media and material validation and tests. The results obtained by the research on media expert validation were 81% and material experts were 81% which were included in the very feasible criteria and student learning outcomes after using scrapbook learning media was increased by 27.94. Before using scrapbook learning media the average student score was 67.58 to 95.52 after using scrapbook learning media. The increase in learning outcomes was calculated using N-Gain which obtained a result of 0.8711 including in high criteria. This result shows that there is an increase in learning outcomes by using scrapbook learning media.